Crop rotation in Guarapuava. X. Effects of winter crops on some agronomic characteristics of soybean plants under direct drilling - Santos, Henrique Pereira dos; Wobeto, Celso; Pereira, Luiz Ricardo (Pesquisa Agropecuaria Brasileira, 1991)
From 1984 up to 1988, at the Cooperativa Agrária Mista Entre-Rios Ltda., in Guarapuava, PR, Brazil, the effects of some crop rotation systems on yield and on other agronomic characteristics of soybean were assessed. Seven cropping systems were tested where soybeans were seeded in succession to different winter crops (white oats, flax, and barley) distributed in several crop rotation systems. Summer crops were direct drilled in plots of 60 m2 and a randomized blocks design with four replications was used: Soybeans grown in the no-till system following white oats, barley and flax showed good yields (2,605 kg/ha). Insertion of the first pods was influenced by the preceding winter crops. All characteristics studied were influenced by the year factor. Excessive straw of white oats and insufficient covering provided by flax made the direct drilling of soybeans difficult, as compared to barley, which provided good soil cover.